Hydration assessment of a semiprofessional male Chilean basketball team during practice - Salinas, H.; Venegas, M. (Sport Performance & Science Reports, 2020)
Practical Applications - If you do not know players` hydration habits outside practice or think they may not be adequately hydrated, make hydration the first practice task. - Control dehydration produced by the practice session by weighing players before and after and calculate relative body weight loss. - Calculate the minimum water intake for each player using the following equation (if you get a negative number, it means the player does not need to drink fluid): Equation 3. Sweat Volume [lt]: [[Bodyweightloss[lt]+Waterintake[lt]]-Urinevolume[lt]] [3 ] - If you do not have individual values for sweat rates, use a sweat rate between 1000 and 1200 ml/hr as a reference to establish hydration strategies for games and practices. - Make sure players always have water available during the practice session. - Prefer rehydration drinks over water because water stimulates urine production, slowing down the rehydration process.